Pengembangan Creativity Idea Based Technology untuk Membentuk Womenpreneur sebagai Upaya Meningkatkan Ekonomi Masyarakat pada Perempuan Dusun Purwo Kabupaten Pasuruan. - Imam Bukhori; Elfia Nora; I Nyoman Suputra; Sopiah Sopiah (STIPAS Tahasak Danum Pambelum Keuskupan Palangkaraya, 2025)
Women's empowerment is a program increasingly promoted by the government. When women are empowered, they will contribute in various sectors, including education, economics, culture, health, the environment, and so on. The presence of female entrepreneurs will shape the presence of women entrepreneurs in each region, bringing new breakthroughs to their respective business fields. The objectives of this community service activity are: 1) To provide knowledge about digital technology that women in Purwo Hamlet, Pasuruan Regency, can use to explore creative entrepreneurial ideas. 2) To provide mentoring and capital assistance for the most creative, original ideas, which will be developed with a systematic business plan and business control. The stages of this community service activity begin with planning, implementation, and evaluation. The results of this community service activity are: 1) The women of Purwo Hamlet, consisting of housewives, teenagers, and adult women who have graduated from school, are very enthusiastic about finding entrepreneurial ideas by opening several business applications on their mobile phones, then designing business ideas or business plans. They are also given modest capital rewards for original ideas. 2) The business plan submitted by the women of Purwo Hamlet related to the natural resources in Purwo Hamlet and what was implemented was young papaya fruit, which was planned to be made into shredded fruit targeting vegetarian consumers.